Borges va al cine - Utrera, Laura Lorena (Imagofagia, 2021)
Sobre Aguilar, Gonzalo y Emiliano Jelicié. Borges va al cine. Buenos Aires, Libraria, 2010, 184 pp. ,ISBN 978-987-26403-0-9. Palabras clave: reseña, Gonzalo y Emilio Jelicié, Borges va al cine.